Actin-Binding Proteins and Disease - dos Remedios, Cris.; dos Remedios, Cris.; Chhabra, Deepak.; Chhabra, Deepak. (Protein Reviews ;, 2008)
This volume, written by experts in the field, is the first to deal with the relationship between human disease and the actin cytoskeleton. It provides overviews of actin and selected actin-binding proteins, and then focuses on diseases that involve these proteins. Specific chapters deal with actin, cofilin, profilin, gelsolin and thymosin ¾4. Other chapters discuss the roles of multiple actin-binding proteins in cancer and metastasis, leukocyte disorders, and heart failure, and there is a chapter that describes how intracellular pathogens use the host actin cytoskeleton. This seminal volume is intended for researchers, clinicians, physicians, and graduate students in the fields of biochemistry, cell biology, microbiology, immunology, and genetics.